2023
DOI: 10.1038/s41598-023-33005-5
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence and treatment of mental disorders in Saudi youth and adolescents

Abstract: Previous global and regional studies indicate that adolescents and young adults (i.e., youth) are affected by various mental disorders with lifelong consequences. However, there are no national estimates of mental disorders prevalent among Saudi youth. Using data from the Saudi National Mental Health Survey (SNMHS), we examined the lifetime prevalence, treatment, and socio-demographic correlates of mental disorders among Saudi youth (aged 15–30). A total of 4004 interviews were conducted using the adapted Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 101 publications
1
2
0
Order By: Relevance
“…In alignment with the data from the Saudi National Mental Health Survey on Saudi youth ( 24 ), our results indicate a higher prevalence of GAD and mean GAD-7 scores among Saudi students compared to non-Saudis. Additionally, Saudi students were more likely to be diagnosed with or suspect undiagnosed mental disorders, which resonates with the broader context of mental health in Saudi Arabia ( 25 ).…”
Section: Discussionsupporting
confidence: 86%
“…In alignment with the data from the Saudi National Mental Health Survey on Saudi youth ( 24 ), our results indicate a higher prevalence of GAD and mean GAD-7 scores among Saudi students compared to non-Saudis. Additionally, Saudi students were more likely to be diagnosed with or suspect undiagnosed mental disorders, which resonates with the broader context of mental health in Saudi Arabia ( 25 ).…”
Section: Discussionsupporting
confidence: 86%
“…Statistical data for the mentally ill in Saudi Arabia shows that the number of mentally ill patients has increased rapidly from 10,245 patients in inpatient units in 2002 to 15,004 in 2004 [2]. More recent data showed that the prevalence of a mental disorder among Saudi youth was 40.10%, where anxiety disorders affected 26.84% of the sample, followed by disruptive behavior disorders (15.44%), mood disorders (9.67%), substance use disorders (4%), and eating disorders (7.06%) [3]. The prevalence of mental disorders among patients who attended primary healthcare centers was 28.5% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Substance use is increasing worldwide and affects people at a young age as proved by surveys in different geographical regions in the world. For instance, Altwaijri et al examined the lifetime prevalence, treatment and socio-demographic correlates of mental disorders among Saudi youth (aged 15-30) and found a 4% prevalence of substance use disorders (SUDs) (1).…”
Section: Introductionmentioning
confidence: 99%